(untitled) (American Journal of Islam and Society, 2023)
The book is comprehensively written for the general reader. The chapters begin with a series of explanations that are followed by additional read-ings on ijtihad-related aspects of shariah relevant to the halal industry. Part I concludes with a chapter on “Islam and Science,” which examines ways in which scientific research can be incorporated into Shariah. Part II states that the Department of Standards Malaysia has issued sixteen halal standards since 2004. Halal pharmaceuticals are a significant com-ponent of the halal industry’s growth. The establishment of halal parks in Malaysia’s various states and strategic locations aims to facilitate the country’s development as well. Part III of the volume analyses regional and international developments in the ASEAN region’s halal industry. Following that, a brief history, development, and diversification of the industry in Malaysia, Indonesia, and Turkey are discussed. The book closes with a summary of the book’s findings and a number of actionable recommendations.